Plasma osteoprotegerin as a biomarker of poor glycaemic control that predicts progression of albuminuria in type 2 diabetes mellitus: A 3-year longitudinal cohort study. (March 2020) - Moh, Angela Mei Chung; Pek, Sharon Li Ting; Liu, Jianjun; Wang, Jiexun; Subramaniam, Tavintharan; Ang, Keven; Sum, Chee Fang; Kwan, Pek Yee; Lee, Simon Biing Ming; Tang, Wern Ee; Lim, Su Chi
Highlights: Poor glycaemic control is associated with elevated risk for vascular complications. Biomarkers for predicting susceptibility to glycaemic deterioration are lacking. Osteoprotegerin (OPG) predicted development of poorly-controlled type 2 diabetes. OPG was independently associated with progression of albuminuria. OPG–albuminuria progression association was mediated by poorly-controlled diabetes. Abstract: Aims: Poor glycaemic control elevates the risk for vascular complications. Biomarkers for predicting susceptibility to glycaemic worsening are lacking. This 3-year prospective analysis assessed the utility of several circulating diabetes-related biomarkers for predicting loss of glycaemic control, and their contribution to albuminuria progression in type 2 diabetes mellitus (T2DM). Methods: T2DM subjects with adequately-controlled diabetes (HbA1c < 8%) at initial recruitment were analysed (N = 859). Baseline plasma levels of osteoprotegerin (OPG), C-reactive protein (CRP), adiponectin, intercellular-cell adhesion molecule-1, and vascular-cell adhesion molecule-1 were quantified using immunoassay. Definitions for development of uncontrolled diabetes and albuminuria progression were HbA1c ≥ 8.0% and increase in albuminuria category at follow-up, respectively. Results: At follow-up, 185 subjects developed uncontrolled diabetes. Higher baseline CRP and OPG levels were observed in the high-risk individuals, and predicted increased risk for developing uncontrolled diabetes. OPG, but not CRP, was associated with albuminuria progression after multivariable adjustment. The relationship was attenuated following adjustment for development of uncontrolled diabetes, which emerged as a significant associate. Mediation analysis revealed that loss of glycaemic control explained 64.5% of the relationship between OPG and albuminuria progression. Conclusions: OPG outperformed other diabetes-related biomarkers to be a potentially useful biomarker for predicting loss of glycaemic control and its associated albuminuria deterioration.